The Happiness of the Sandwich Generation in Bali: the Roles of Family, Social, and Balinese Culture - Yuniari, Ni Komang Ayu; Saskara, Ida Ayu Nyoman (Signifikan: Jurnal Ilmu Ekonomi, 2023)
The sandwich generation in Bali, especially Gianyar, which is still thick with its culture, has a dual role in the family, as caregivers for children and parents, breadwinners, and is actively involved in community activities. This study aims to analyze the influence of cultural norms in moderating the effect of family roles and social support on the happiness of the sandwich generation. The samples were 203 generations of sandwiches obtained through accidental sampling techniques and analyzed using Moderated Regression Analysis (MRA). The results showed that cultural norms, social support, and family roles significantly influence the happiness of the sandwich generation. Meanwhile, cultural norms were not variables that moderate the effect of family roles and social support on the happiness of the sandwich generation. This study proposed two central policies to break the sandwich generation chain in Gianyar Regency: socializing the importance of financial literacy so that in the future, a person does not depend on his child for life and forming a parent empowerment group to reduce the burden of the sandwich generation.JEL Classification: M14, J12, I31, L31How to Cite:Yuniari, N. K. A., & Saskara, I. A. N., (2023). Happiness of the Sandwich Generation in Bali: the Role of Family, Social and Balinese Culture. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 355-370. https://doi.org/10.15408/sjie. v12i2.32315.